2015
DOI: 10.7314/apjcp.2015.16.13.5565
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between ERCC5 rs17655 Polymorphism and Colorectal Cancer Risk: Evidence Based on a Meta-analysis

Abstract: Background: Previous studies evaluating the association between the excision repair cross complementing group 5 (ERCC5) gene rs17655 polymorphism and colorectal cancer susceptibility generated controversial results. To generate large-scale evidence on whether the ERCC5 rs17655 polymorphism might indeed be associated with colorectal cancer susceptibility, the present meta-analysis was performed. Materials and Methods: Data were collected from PubMed, Embase and Web of Science, with the last report up to Apr 03,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We found a certain genotype of rs751402 to increase gastric cancer risk significantly in comparison to the wild-type sequence. Previous studies have investigated associations between ERCC5 gene polymorphisms and risk of various cancers (Luo et al, 2013;Liang et al, 2014;Lu et al, 2014;Na et al, 2015;Zeng et al, 2015). Luo et al (2013) conducted a case-control study to assess the influence of several single nucleotide polymorphisms of DNA repair genes on glioma risk, finding that the ERCC5Asp1558Hisvariation is connected to susceptibility to this cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a certain genotype of rs751402 to increase gastric cancer risk significantly in comparison to the wild-type sequence. Previous studies have investigated associations between ERCC5 gene polymorphisms and risk of various cancers (Luo et al, 2013;Liang et al, 2014;Lu et al, 2014;Na et al, 2015;Zeng et al, 2015). Luo et al (2013) conducted a case-control study to assess the influence of several single nucleotide polymorphisms of DNA repair genes on glioma risk, finding that the ERCC5Asp1558Hisvariation is connected to susceptibility to this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lu et al (2014) carried out a case-control investigation in a Chinese population, from which they concluded that certain variants of this same polymorphism are associated with increased risk of laryngeal cancer. In a separate Chinese case-control study, Na et al (2015) failed to connect rs751402 with breast cancer risk, while a nine-study meta-analysis conducted by Zeng et al (2015) suggested that the ERCC5 rs17655 polymorphism might contribute to colorectal cancer genetic susceptibility. Two reports have tested the association between ERCC5 gene polymorphisms and gastric cancer development, but with inconclusive results (Hussain et al, 2009;Duan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the ERCC5 rs17655 polymorphism has important roles in the development of several kinds of cancer, such as colorectal cancer, uterine cervical cancer, lung cancer, laryngeal cancer, as well as breast cancer (Li et al, 2014;Liang et al, 2014;Joo et al, 2015;Na et al, 2015;Zeng et al, 2015). Li et al (2014) reported that the ERCC5 rs17655 polymorphism is correlated with susceptibility to laryngeal cancer, while Joo et al (2015) conducted a study in a Korean population, and found that it was associated with the development of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2014) reported that the ERCC5 rs17655 polymorphism is correlated with susceptibility to laryngeal cancer, while Joo et al (2015) conducted a study in a Korean population, and found that it was associated with the development of cervical cancer. Zeng et al (2015) conducted a meta-analysis of 9 studies, and found that this polymorphism might influence the development of colorectal cancer. In contrast, a previous metaanalysis of 44 published case-control studies reported that the ERCC5 rs17655 polymorphism did not influence cancer risk (Zhu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%